Fabrication of Zinc oxide thin films by sol-gel dip coating process - Oloruntoba, Sola Omodele; Zainal, Zulkarnain; Sulaiman, Yusran; Mohd Zawawi, Ruzniza (Scientific Research and Community, 2024)
Zinc oxide (ZnO) is a non-toxic material known for its distinctive physical and chemical properties, including a direct band gap energy of 3.37 eV and a large exciton binding energy of 60 meV, which contribute to its significant thermal and chemical stability at room temperature. Due to these characteristics, ZnO plays a critical role in various applications, such as UV light emitters, transparent conducting thin films in electronic devices, gas sensors, piezoelectric materials, transducers, and as a transparent conductive oxide (TCO) layer in thin-film photoelectrochemical cells. Numerous fabrication techniques have been employed to produce ZnO thin films. However, many of these methods require costly equipment, high vacuum environments, and elevated temperatures. In contrast, the sol-gel process stands out as a convenient, cost-effective, and versatile method for ZnO thin film fabrication. It offers advantages such as simplicity, low crystallization temperature, ease of reproducibility, molecular-level homogeneity, and precise compositional control. In this study, ZnO thin films were deposited onto Indium Tin Oxide (ITO) glass substrates using the sol-gel dip coating method, with varying preparative parameters: sol concentrations and annealing temperatures. The resulting samples were characterized using a UV-visible spectrophotometer, X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), and energy dispersive X-ray spectroscopy (EDX). The results demonstrated that the unique properties of ZnO thin films are highly dependent on the preparative parameters. Specifically, the band gap energy decreased from 3.25 eV to 3.18 eV with increasing sol concentration and also showed a similar decline with higher annealing temperatures. XRD patterns revealed a smaller full width at half maximum (FWHM) of the most intense peak (002) at higher sol concentrations and annealing temperatures, indicating an increase in crystallite size. FESEM images highlighted distinct morphological changes corresponding to the variations in sol precursor concentration and annealing temperature, while EDX analysis confirmed the formation of highly pure ZnO thin films on ITO glass substrates.